Preservation techniques and their impact on bee pollen chemical and microbiological composition - Lema, Filipe (2020)
Bee pollen has been used as a food supplement for many years because of its antioxidant, antibacterial and antifungal properties, and is currently undervalued in the Portuguese market compared to honey. This may be partly explained by the lack of information on the benefits of pollen and on the influence of preservation methods on composition and chemical quality. Therefore, this work will evaluate the possible impact of various preservation techniques, namely freezing, oven drying at 35ºC, 40ºC and 45ºC and freeze-drying, on the chemical composition and microbiological load of the pollen.